Feasibility study and design of natural dehumidification method using desiccant for model house - Mohammed Amirul Faeez Norazmi (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This case or research is feasibility study and design of natural dehumidification method using desiccant for model house. Desiccant dehumidification is function to improvise the nowadays heating, ventilation and air conditioning (HVAC) industry became well. Desiccant dehumidification cooling system improvise and increase the performance of vapour compression system that use in coventation air conditioning.The desiccaent dehumidification system have two type which is solod and liquid desiccant cooling system. Desiccant dehumidifier based evaporative coolers can reduce air conitioning operation cost because since the energy need to power the desiccant cooling system is small and the source of this required acn be renewable (solar energy, waste heat, natural gas). This technology become increase attractive due to its high effcient used of low-grade energy and its effectiveness in dehumidification that cause energy efficaiency of air conditionning increased .The equation is used to calculate the data for psychrometric condition and then analyse th data to plot the graph to show the result of our caculation.